Post-wildfires effects on physicochemical properties of surface water: the case study of Zêzere watershed (Portugal). Issue 1 (2nd January 2019) - Meneses, Bruno M.; Reis, Eusébio; Reis, Rui; Vale, Maria J.
ABSTRACT: In Portugal, wildfires are frequent and sometimes catastrophic and responsible for high damages and human losses. They have been especially intense in the Center Region of Portugal, where the Zêzere watershed is located. This research presents an analysis of the temporal and spatial occurrence of these events within the watershed. It was observed that the extent of the burned areas has a high annual variation and is not directly related to the number of reported occurrences. However, considering these factors and the high incidence of these events in some delimited sectors, environmental stress is observed, especially on the surface water quality. Water quality deterioration in the main water bodies is particularly relevant within the areas where drinking water reservoirs are located. The water quality parameters (WQPs) collected by the water quality monitoring stations (WQSs) located in these sectors (data from SNIRH) were cross-referenced with the burned areas recorded annually. Variations in the physicochemical properties of the surface water were analyzed, depending on the occurrence of wildfires and their corresponding burned areas. The increase of certain WQP downstream of watercourses that intersect sub-basins with burned areas also demonstrates the straight relation between wildfires and an increasing risk for water quality.